Ankle Ligament Reconstruction-Return to Sport After Injury (ALR-RSI) Scale and Return to Sports After Ankle Ligament Reconstruction or Repair – A Systematic Review - YuChia Wang MA; Maximilian Hinz MD; Wyatt H. Buchalter; Amelia H. Drumm; Emre A. Eren MD; C. Thomas Thomas Haytmanek MD; Jonathon D. Backus MD FAAOS (Foot & Ankle Orthopaedics, 2024)
Category: Ankle; Sports Introduction/Purpose: While objective outcome measures assessing foot and ankle function are well established to determine return to sport (RTS) following ankle injuries, psychological factors have been recognized in recent years to be equally important. The Return to Sport after Injury (RSI) scale has become an emergingly useful tool used in assessing psychological readiness to return to sporting activity after various pathologies and their treatment. The Ankle Ligament Reconstruction-Return to Sport after Injury (ALR-RSI) scale is a novel questionnaire and scoring system for the evaluation of psychological readiness to return to sport following lateral ankle ligament reconstruction or repair. Purpose: To systematically review existing literature regarding the ALR-RSI scale and to assess its correlation with RTS and functional outcomes as well as feasibility, reliability, and consistency. Methods: A systematic review of the literature based on the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) was conducting using PubMed, Embase and Cochrane Library. Studies that evaluated psychological readiness after ankle ligament reconstruction or repair for the treatment of chronic lateral ankle instability using the ALR-RSI scale were included. The results from each study were pooled, and weighted means and overall rates were calculated. Results: In total, 157 patients (53.2% male, mean age: 34.2 years) from 3 articles were included. Overall, 85.0% of patients reported successful RTS, but only 48.9% of patients returned to the preoperative sporting level. All studies reported a significant difference in psychological scores between patients who returned to sport and those who didn’t. The pooled mean functional outcome measures, reported as the American Orthopaedic Foot and Ankle Society Ankle-Hindfoot (AOFAS) Score and Karlsson-Peterson Score, were 82.7 (range, 29-100) and 81.7 (range, 25-100), respectively. The ALR-RSI scale demonstrated strong correlations with the AOFAS Score and Karlsson-Peterson Score. Conclusion: Patients who RTS after ankle ligament reconstruction or repair exhibited higher psychological readiness compared to those who didn’t return to sport. The ALR-RSI scale showed strong correlations with ankle function. Evaluation of psychological readiness using the ALR-RSI scale may provide an additional tool in the rehabilitation process of athletes that aim to assess RTS after ankle ligament reconstruction or repair.